2022
DOI: 10.1037/fsh0000665
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of family resilience, emotional, behavioral, and developmental concerns and emergency room visits for children with asthma.

Abstract: Introduction:The current study fills a gap in the literature by examining relations among physical health and resilience factors, family functioning, emergency visits, and mental health problems for youth with asthma. The study purpose was to assess associations among four predictors-asthma severity, body mass index (BMI), having an adult mentor, and ability to make and keep friends-and 3 three outcomes-family resilience, emotional, behavioral and developmental concerns, and emergency room (ER) visits among yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Furthermore, the significant rise in the number of hospital admissions because of asthma may reflect an increase in asthma severity, poor asthma management, limited access to primary care, and/or the effect of poverty [ 19 ]. On the other hand, countries that have developed asthma management strategies have observed decreases in hospital admission rates due to asthma [ 20 ]. Because there are a few published studies from Saudi Arabia concerning the variation in factors related to asthma exacerbation among the Saudi pediatric population, we aim to explore the variations in the factors affecting asthma exacerbations and other atopic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the significant rise in the number of hospital admissions because of asthma may reflect an increase in asthma severity, poor asthma management, limited access to primary care, and/or the effect of poverty [ 19 ]. On the other hand, countries that have developed asthma management strategies have observed decreases in hospital admission rates due to asthma [ 20 ]. Because there are a few published studies from Saudi Arabia concerning the variation in factors related to asthma exacerbation among the Saudi pediatric population, we aim to explore the variations in the factors affecting asthma exacerbations and other atopic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that individuals with increased psychological hardiness experience lower levels of anxiety related to treatment (24). The psychological hardiness and distress tolerance of mothers who have hard of hearing children, combined with the multitude of behavioral challenges they face, the lack of social, educational, and financial resources, and the psychological pressures they encounter, give rise to numerous risk factors for both the parents and the children.…”
Section: Introductionmentioning
confidence: 99%